A formação de professores da Educação do/no campo: território em disputa legal - Melo, Maria Aparecida Vieira de; Almeida, Ricardo Santos de (Revista Espaço Acadêmico, 2019)
O presente artigo visa compreender como está presente as regularidades e dispersões na prática discursiva dos enunciados no marco legal para educação do campo. Problematiza, através de um procedimento analítico-argumentativo, a legislação educacional voltada para fomentar a formação dos professores da educação do/no campo. Argumenta que, há um respaldo legal para efetivação da educação como direito público subjetivo para os povos do campo, a partir da mobilização dos movimentos sociais por uma educação básica do campo. Através da análise arqueológica do discurso (FOUCAULT, 2000) conclui-se como achado uma regularidade nos enunciativos do marco legal voltados para educação do/no campo, em detrimento das dispersões enunciativas que legitimam a falta de formação de professores nos mais diversos territórios, legitimando, portanto, a disparidade existente entre o enunciado e a materialidade da educação do/no campo, tal como suscita os movimentos sociais. The training of teachers of the Education of / in the field: territory in legal dispute Abstract: This article aims to understand how the regularities and dispersions are present in the discursive practice of the statements in the legal framework for rural education. It proposes an analytical-argumentative procedure to study educational legislation aimed at promoting the education of teachers in the field. He argues that there is legal support for the realization of education as a subjective public right for the rural people, from the mobilization of social movements for a basic education of the countryside. The archaeological analysis of discourse (FOUCAULT, 2000) concludes as a regularity in the enunciates of the legal framework focused on education in the field, to the detriment of the enunciative dispersions that legitimize the lack of teacher training in the most diverse territories, legitimating, therefore, the disparity between the statement and the materiality of the education of the field, as it arouses social movements. Keywords: Legislation; Social movements; Archaeological discourse analysis.